2003
DOI: 10.1097/01.lab.0000079784.81186.b9
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin Is a Key Mediator of Prostate Growth and Male Reproductive Tract Development

Abstract: SUMMARY:Male mice deficient in relaxin showed retarded growth and marked deficiencies in the reproductive tract within 1 month of age. At 3 months of age, male reproductive organ weight (including the testis, epididymis, prostate, and seminal vesicle) from relaxin null (RLXϪ/Ϫ) mice were significantly (p Ͻ 0.05) smaller than those of wild-type (RLXϩ/ϩ) male mice. Histologic examination of RLXϪ/Ϫ mouse tissues demonstrated decreased sperm maturation (testis), increased collagen, and decreased epithelial prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
86
4
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 54 publications
6
86
4
2
Order By: Relevance
“…They also showed a decreased epithelial proliferation in the prostate and decreased sperm maturation [14]. These studies suggested that relaxin lack could produce local fibrosis in the prostate gland and in testes, but the following study by Ganesan et al [15] do not observe the same results.…”
Section: Relaxin and Reproduction In Malescontrasting
confidence: 39%
See 1 more Smart Citation
“…They also showed a decreased epithelial proliferation in the prostate and decreased sperm maturation [14]. These studies suggested that relaxin lack could produce local fibrosis in the prostate gland and in testes, but the following study by Ganesan et al [15] do not observe the same results.…”
Section: Relaxin and Reproduction In Malescontrasting
confidence: 39%
“…Deficiency of relaxin in males remains controversial: Samuel et al [14] studied Rln -/-male mice and wild-type Rln +/+ and found a decrease in prostate, testis epididymis and seminal vesicles weight in Rln -/-mice. They also showed a decreased epithelial proliferation in the prostate and decreased sperm maturation [14].…”
Section: Relaxin and Reproduction In Malesmentioning
confidence: 99%
“…First, considering that the murine M1 relaxin peptide is a hormone critical for mouse prostate growth and development, 17 it is possible that the high H2 relaxin levels in the PC3-Luc-H2/eGFP-derived tumors may trigger in vivo prostate growth mimicking that which occurs during early development. Second, the high H2 relaxin levels in PC3-Luc-H2/eGFP cell-derived tumors may indirectly stimulate the formation of tumor vasculature thereby providing a platform for enhanced tumor cell growth through the upregulation of effectors such as VEGF and NOS, for example.…”
Section: Discussionmentioning
confidence: 99%
“…17 Male mice deficient for murine M1 relaxin (equivalent is H2 relaxin) exhibit retarded growth and marked deficiencies in the reproductive tract, including the testis, epididymis, prostate and seminal vesicles. 17 In the human, relaxin has also been found to be consistently secreted into seminal fluid at levels of 50 ng/mL, which has been correlated with enhancing the capacity for sperm motility. 18 Recently, the relaxin receptor (LGR7) was cloned and found to be coexpressed with H1/H2 relaxins in the prostate.…”
mentioning
confidence: 99%
See 1 more Smart Citation